2019
DOI: 10.6018/analesps.348441
|View full text |Cite
|
Sign up to set email alerts
|

Health and burnout of home health care assistants: impact of a training intervention

Abstract: Título: Salud y burnout de cuidadores profesionales a domicilio: Impacto de una intervención formativa. Resumen: Existe una creciente necesidad de cuidados en los países desarrollados, por lo que el número de cuidadoras a domicilio ha aumentado de manera exponencial. La literatura ha señalado que este grupo profesional tiene un alto riesgo de sufrir una gran variedad de problemas de salud. A pesar de su importancia, no hay cursos de entrenamiento descritos para ellas. Este estudio describe el diseño de un curs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Staff training has been shown to be associated with improved patient outcomes [32], and it could also exert beneficial effects on the health of home care workers themselves. A study of 29 home care assistants in Spain reported that a program with 13 weekly training sessions was able to reduce their dysfunctional thoughts about care, which could be acted as mediators in caregiving stress [33]. Furthermore, a study on 25 hospital social workers found that professional skill-development training was able to alleviate burnout [34].…”
Section: Discussionmentioning
confidence: 99%
“…Staff training has been shown to be associated with improved patient outcomes [32], and it could also exert beneficial effects on the health of home care workers themselves. A study of 29 home care assistants in Spain reported that a program with 13 weekly training sessions was able to reduce their dysfunctional thoughts about care, which could be acted as mediators in caregiving stress [33]. Furthermore, a study on 25 hospital social workers found that professional skill-development training was able to alleviate burnout [34].…”
Section: Discussionmentioning
confidence: 99%